Miradas de inspección: las bibliotecas populares del partido de La Plata según los informes de la Comisión Protectora, 1919-1945 - Fiebelkorn, Ayelén (2018)
Between the decades of 1910 and 1940, in the neighborhoods of different Argentine cities, hundreds of popular libraries were founded and obtained the protection of the Protective Commission of Popular Libraries (state agency of the Ministry of Justice and Public Instruction). In this article, we will deal with the different inspection reports that the inspectors of said Commission elaborated from their visits to the popular libraries of the Party of La Plata (Capital of the Province of Buenos Aires) between 1919 and 1945, period of expansion of the city and the number of libraries.; Trying to exceed - without neglecting - the descriptive plan that this type of documentary source can offer us (date of foundation, quantity and quality of books, aspect of library rooms, etc.), we start from the concept of look(s), which It allows us to attend to the attributions of senses operated by these officials regarding the popular libraries inspected, their neighborhood insertion contexts, their leaders, and their bibliographic material.